Relationship between nutritional status and myopia degree in adolescents at Prof. CPL USU Hospital - Herryanto, Carvin; Aldy, Fithria; Amra, Aryani Atiyatul (International Journal Labs, 2023)
Myopia is currently a major global public health problem causing significant vision loss and is a risk factor for more serious ocular conditions. Weight gain in adolescents has increased significantly in recent years due to lack of physical activity, increased caloric intake, and comfort in indoor environments. Weight gain is also the most common cause of dyslipidemia in adolescents. This is an observational analytic study with a cross sectional design. The study was conducted at Prof. CPL Universitas Sumatera Utara General Hospital from March 2023 until July 2023. Data analysis was carried out analytically and presented in the form of data tabulations. This study was attempted by 50 subjects with myopia who visited the Eye Polyclinic. Most of the subjects in this study were female, totaling 26 people (52%). The mean age of the subjects was 20.92 years with the youngest was 13 years old and the oldest was 24 years old. The mean height and weight measurements respectively were 1.63+0.1 m and 68.74+19.87 kg. Based on body mass index, most of the subjects were in normal cathegories accounted for 20 subjects (40%). Based on cholesterol levels, subjects with mild myopia showed a mean value of 206.84 mg/dL, those with moderate myopia had a mean of 190.94 mg/dL and severe myopia had a mean of 207.36 mg/d. Nutritional status have no significant correlation to the degree of myopia in adolescents at Prof. CPL Universitas Sumatera Utara General Hospital.